Neurological soft signs, dissociation and alexithymia in patients with obsessive-compulsive disorder (OCD) and healthy subjects. (February 2018) - Tapancı, Zafer; Yıldırım, Abdullah; Boysan, Murat
Abstract: A body of evidence has supported that patients with obsessive-compulsive disorder (OCD) have increased rates of various neurological soft signs (NSS) compared to controls. Various lines of research has documented robust relationships between OCD and dissociative symptomatology. The study aimed to examine the associations between obsessive-compulsive symptoms, dissociative experiences alexithymia, and NSS. The study included thirty OCD patients and thirty healthy controls, matched for age, marital status, education, and income. The Neurological Evaluation Scale (NES), Padua Inventory-Revised (PI-R), Dissociative Experiences Scale (DES) and Toronto Alexithymia Scale (TAS-20) were administered. In comparison to healthy controls, patients with OCD had difficulty sequencing for complex motor acts and greater absorption/ imaginative involvement. Using latent class analysis, the study sample was classified into two homogenous subsets as mild NSS (n = 45) and severe NSS (n = 15). Majority of the participants who were grouped into severe NSS latent class were OCD patient (n = 14, 93.3%). Furthermore, those with severe NSS reported greater levels of alexithymia and more severe obsessive-compulsive symptoms, particularly precision. We concluded that relationships between OCD severity and NSS appear to be of crucial importance. Our data along with accumulated evidence suggest that OCD associated with pronounced NSS may represent a specific subtype of the disorder. Highlights: Obsessive-compulsive disorder (OCD) patients reported significantly greater neurological soft signs (NSS) than controls. Sequencing for complex motor acts and absorption were significant predictors of a principal diagnosis of OCD. Subjects with severe NSS reported more frequent checking and precision, and greater alexithymia than those with mild NSS. When the partial relations were considered, precision was the significant correlate of NSS. NSS suggesting a neurodevelopmental origin may reflect a specific subtype in OCD.